2023
DOI: 10.1007/s10745-022-00388-4
|View full text |Cite|
|
Sign up to set email alerts
|

Land-System Changes and Migration Amidst the Opium Poppy Collapse in the Southern Highlands of Oaxaca, Mexico (2016-2020)

Abstract: For decades, Mexico has been one of the major illegal opium poppy cultivation countries in the world. In 2017-2018 the price of the opium gum dropped abruptly to a historical low, causing a sudden collapse of production. We analyze the dynamics of rural land systems amid this price collapse through a multi-site approach in three neighboring municipalities in the Southern Highlands of the state of Oaxaca, Mexico. We use medium-scale spatial resolution satellite imagery for a quantitative assessment in a five-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…In Peru, a slump in world coffee prices induced coffee growers to migrate to coca-growing areas of the country (Grisaffi & Farthing, 2021;Taj, 2019) (section 2.2). In Mexico, one study found that increased price competition and the abolition of agricultural subsidies drove farmers to migrate to cities or to the USA, with nonmigrating farmers becoming involved in illicit crops (Grandmaison et al, 2019, p. 6) (section 2.2), while another study found that changes in drug consumers' preferences in the USA led to the collapse of the poppy industry and significant out-migration in some villages (Tamariz et al, 2023) (section Error! Reference source not found.…”
Section: Migrationmentioning
confidence: 99%
“…In Peru, a slump in world coffee prices induced coffee growers to migrate to coca-growing areas of the country (Grisaffi & Farthing, 2021;Taj, 2019) (section 2.2). In Mexico, one study found that increased price competition and the abolition of agricultural subsidies drove farmers to migrate to cities or to the USA, with nonmigrating farmers becoming involved in illicit crops (Grandmaison et al, 2019, p. 6) (section 2.2), while another study found that changes in drug consumers' preferences in the USA led to the collapse of the poppy industry and significant out-migration in some villages (Tamariz et al, 2023) (section Error! Reference source not found.…”
Section: Migrationmentioning
confidence: 99%